Pengaruh Gaya Kepemimpinan Manajer, Pola Komunikasi dalam Organisasi, dan Jenis Penghargaan terhadap Loyalitas Karyawan - Irvianti, Laksmi Sito Dwi; Chandranegara, Kokoh (Bina Nusantara University, 2010)
PT Citra Transpor Nusantara is a national private company engaged in public transport services, particularly in the management of taxi meters. This study will analyze both individually and simultaneously the influence of manager leadership style, communication patterns within the organization and type of awards for employee loyalty. The study takes place at PT Citra Transpor Nusantara using correlation and multiple regression methods. Various data are collected and analyzed from respondents namely employees regarding assessment of employee loyalty using Likert scale. The results of this study indicate there is a positive relationship and strong and significant influence between patterns of communication within the organization and the type of awards for employee loyalty. This study also proves the strength of connection and influence between the types of award for employee loyalty was ranked top, second, strength of connection and influence between communication patterns within the organization towards employee loyalty, and third, strength of connection and influence between leadership style towards employee loyalty. The study is expected to give input and suggestions for PT Citra Transpor Nusantara for the management and employees in improving employee loyalty at PT Citra Transpor Nusantara.